THE IMPACT OF GENERATIONAL DIVERSITY ON EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL COMMITMENT - Muxtorova Maftuna Saidmurod qizi (Modern American Journals, 2026)
This study investigates how generational diversity influences employee engagement and organizational commitment among HR managers in Uzbekistan. Using a positivist correlational design, data from 100 HR managers across sectors revealed neutral perceptions of diversity practices (M=2.61-3.21), low scale reliabilities (α<0.3), negligible correlations (r<0.13), and non-significant regression effects (R²=0.055). Exploratory factor analysis identified five factors explaining 62.8% variance, indicating multidimensional constructs. Findings challenge direct impacts, urging refined measures and contextual strategies like mentoring. Null results highlight measurement issues and Uzbekistan's emerging HR maturity, offering practical insights for inclusive policies.
Keywords: rect impacts, urging refined measures and contextual strategies